Formation of a one-dimensional hole channel in MoS2 by structural corrugation. (1st January 2023) - Gao, Yanlin; Nakajima, Haruna; Maruyama, Mina; Taniguchi, Takashi; Watanabe, Kenji; Kitaura, Ryo; Okada, Susumu
Abstract: We have investigated the energetics and electronic structure of monolayer MoS2 with periodic structural corrugations by density functional theory. The total energy of corrugated MoS2 slightly increases with increasing corrugation height, which indicates that the MoS2 sheet intrinsically and extrinsically possesses nanometer scale structural corrugation. The corrugation causes an upward shift of the valence band edge and a downward shift of the conduction band edge owing to the local strain at the wrinkle peak. Accordingly, by injecting holes using the external electric field, the corrugation leads to a one-dimensional conducting channel in the MoS2 sheet. This indicates that corrugation is a plausible procedure to control the dimensionality of the electrons and holes in two-dimensional materials without implementing one-dimensional boundary conditions.